Diagnostic utility of CT for suspected immune checkpoint inhibitor enterocolitis - Michael Dougan; Meghan J Mooradian; Leyre Zubiri; Sienna M Durbin; Nisanard Pisuchpen; Donald F Chute; Florian Johannes Fintelmann; Avinash Kambadakone (Journal for ImmunoTherapy of Cancer)
Background and aims Immune checkpoint inhibitor (ICI) enterocolitis is a common immune-related adverse event and can be fatal, especially when not diagnosed and treated promptly. The current gold standard for diagnosis is endoscopy with biopsy, but CT scan is a possible alternative. The primary objective of this study is to identify the diagnostic performance of CT in the evaluation of ICI enterocolitis.Methods With institutional review board approval, we conducted a retrospective cohort study of patients who received ICI therapy between 2015 and 2019 across a healthcare system. Patients were included if they underwent both abdominal CT and endoscopy with biopsy within 3 days. The radiological and pathological diagnoses, as well as clinical characteristics, were extracted from the electronic medical record. We calculated the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of CT for diagnosing ICI enterocolitis when compared with tissue diagnosis.Results Of the 4474 patients screened, 138 met inclusion criteria. Most common tumor types were melanoma (37%) and lung cancer (19%). Seventy-four per cent were treated with antiprogrammed cell death (PD-1)/PD-L1 therapy. Thirty-nine per cent had signs of enterocolitis on CT scan and 58% had biopsy-proven ICI enterocolitis. Sensitivity and specificity of CT were 50% and 74%, respectively. PPV was 73% and NPV was 52%. Of those with confirmed ICI enterocolitis, 70% had grade 3 or higher symptoms, 91% received steroids and 40% received infliximab.Conclusion The performance of CT scan for diagnosis of ICI enterocolitis is moderate to poor and does not replace endoscopy with biopsy.